1997
DOI: 10.1002/clc.4960200307
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability as a measure of autonomic nervous system function in anorexia nervosa

Abstract: Background and hypothesis: Alteration in sympathovagal balance may be a mechanism of increased cardiovascular mortality and sudden death of patients with anorexia nervosa. This study was undertaken to characterize cardiac autonomic control in patients with anorexia nervosa by means of heart rate variability analysis. Methods: Heart period variability by 24‐h Holter recording was evaluated in 13 young women with anorexia nervosa, 10 constitutionally thin women, and 10 women of normal weight. Results: High‐frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 19 publications
7
84
0
1
Order By: Relevance
“…The present finding is consistent with previous results that eating disorder patients have symptoms of vagal hyperactivity [23][24][25][26]. This sympathovagal imbalance may contribute in part to cardiac autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present finding is consistent with previous results that eating disorder patients have symptoms of vagal hyperactivity [23][24][25][26]. This sympathovagal imbalance may contribute in part to cardiac autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, repolarisation abnormalities and prolongation of ECG Q-T interval are thought to be associated with ventricular arrhythmia and severe weight loss [26,32]. However, a number of studies of HRV have confirmed that these structural and functional abnormalities of the cardiovascular system provoked by AN are reversible after weight restoration [9,25,28,29,33]. This study indicated that HRV in ED patients is lower than control, especially HRV complexity measured by Sample Entropy.…”
Section: Discussionmentioning
confidence: 68%
“…11,12 Electrocardiographic abnormalities are present in most adolescents with AN. 3,4,6,7 Sinus bradycardia is reported to be present in 35-95% of adolescents with AN, 1,[3][4][5] and is believed to be due to the reported increased vagal tone 4,9,10 and decreased metabolic rate.…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…However, the studies in AN patients primarily utilized linear methods to evaluate sympathovagal balance. Several of these studies have reported decreased vagal tone whilst others found an increase in parasympathetic activity [21,22,6,[23][24][25]. Other studies report no change or altered sympathovagal balance [26,27].…”
Section: Introductionmentioning
confidence: 99%